2012
DOI: 10.1016/j.plaphy.2012.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of dehydration responsive element binding proteins (StDREB2) confers higher tolerance to salt stress in potato

Abstract: Dehydration responsive element binding proteins (DREB) are members of a larger family of transcription factors, many of which have been reported to contribute to plant responses to abiotic stresses in several species. While, little is known about their role in potato (Solanum tuberosum). This report describes the cloning and characterization of a DREB transcription factor cDNA, StDREB2, isolated from potato (cv Nicola) plants submitted to salt treatment. Based on a multiple sequence alignment, this protein was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 60 publications
3
49
0
Order By: Relevance
“…Results of biochemical analysis indicated significant increase in proline and total free amino acids under salt stress, in agreement with the results of Daneshmand et al (2010), Bouaziz et al (2012) and Marcek et al (2014). The increase in amino acids in potato plantlet under salt stress was also reported by Asensi-Fabado et al (2014).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Results of biochemical analysis indicated significant increase in proline and total free amino acids under salt stress, in agreement with the results of Daneshmand et al (2010), Bouaziz et al (2012) and Marcek et al (2014). The increase in amino acids in potato plantlet under salt stress was also reported by Asensi-Fabado et al (2014).…”
Section: Discussionsupporting
confidence: 87%
“…Bouaziz et al (2012) and Marcek et al (2014) reported an increase in proline accumulation. Also, Asensia-Fabado et al (2014) found increase in total free amino acids with salinity stress.…”
Section: Introductionmentioning
confidence: 94%
“…The His-tag fusion protein was purified by Ni-NTA affinity chromatography and the gel mobility shift assays were performed as described previously (Bouaziz et al 2012).…”
Section: Measurement Of Soluble Sugar Contentmentioning
confidence: 99%
“…We have focused on potato ERF genes because of the economic importance of this plant species worldwide (Bouaziz et al 2012(Bouaziz et al , 2013(Bouaziz et al , 2015Charfeddine et al 2015a, b).…”
Section: Introductionmentioning
confidence: 99%
“…The ectopic expression of these genes in potato conferred enhanced tolerance to salt stress in transgenic plants (Bouaziz et al 2012(Bouaziz et al , 2013.…”
Section: Introductionmentioning
confidence: 99%